Polarisation independent resistively loaded frequency selective surface absorber with optimum oblique incidence performance - Zabri, Normi; Cahill, Robert; Schuchinsky, Alexander (Institution of Engineering and Technology, 2014)
This study presents the design of a thin electromagnetic absorber which exhibits radar backscatter suppression that is independent of the wave polarisation at large incidence angles. The structure consists of a metal backed printed frequency selective surface (FSS), with resistors placed across narrow gaps inserted in the middle of each of the four sides of the conductor loops. The geometry of the periodic array and the value of the vertical and horizontal resistor pairs are carefully chosen to present a real impedance of 377 Ω at the centre operating frequency for both TE and TM polarised waves. Angular sensitivity and reflectivity bandwidth have been investigated for FSS absorber designs with thicknesses of 1, 2 and 3 mm. Each of the three structures was optimised to work at a centre frequency of 10 GHz and an incident angle of 45°. The design methodology is verified by measuring the radar backscatter suppression from a 3 mm (λ / 10) thick screen in the frequency range 8–12 GHz. The absorber construction was simplified by filling the four metal gaps in each unit cell with shielding paint, and selecting the ink thickness to give the two required surface resistance values.